Colchicine for prevention of vascular inflammation in Non-CardioEmbolic stroke (CONVINCE) – study protocol for a randomised controlled trial. (June 2021) - Kelly, Peter; Weimar, Christian; Lemmens, Robin; Murphy, Sean; Purroy, Francisco; Arsovska, Anita; Bornstein, Natan M; Czlonkowska, Anna; Fischer, Urs; Fonseca, Ana Catarina; Forbes, John; Hill, Michael D; et al.
Background: Inflammation contributes to unstable atherosclerotic plaque and stroke. In randomised trials in patients with coronary disease, canukinumab (an interleukin-1B antagonist) and colchicine (a tubulin inhibitor with pleiotropic anti-inflammatory effects) reduced recurrent vascular events. Hypothesis: Anti-inflammatory therapy with low-dose colchicine plus usual care will reduce recurrent vascular events in patients with non-severe, non-cardioembolic stroke and TIA compared with usual care alone. Design: CONVINCE is a multi-centre international (in 17 countries) Prospective, Randomised Open-label, Blinded-Endpoint assessment (PROBE) controlled Phase 3 clinical trial in 3154 participants. The intervention is colchicine 0.5 mg/day and usual care versus usual care alone (antiplatelet, lipid-lowering, antihypertensive treatment, lifestyle advice). Included patients are at least 40 years, with non-severe ischaemic stroke (modified Rankin score ≤3) or high-risk TIA (ABCD2 > 3, or positive DWI, or cranio-cervical artery stenosis) within 72 hours-28 days of randomisation, with qualifying stroke/TIA most likely caused by large artery stenosis, lacunar disease, or cryptogenic embolism. Exclusions are stroke/TIA caused by cardio-embolism or other defined cause (e.g. dissection), contra-indication to colchicine (including potential drug interactions), or incapacity for participation in a clinical trial. The anticipated median follow-up will be 36 months. The primary analysis will be by intention-to-treat. Outcome: The primary outcome is time to first recurrent ischaemic stroke, myocardial infarction, cardiac arrest, or hospitalisation with unstable angina (non-fatal or fatal). Summary: CONVINCE will provide high-quality randomised data on the efficacy and safety of anti-inflammatory therapy with colchicine for secondary prevention after stroke. Schedule: First-patient first-visit was December 2016. Recruitment to complete in 2021, follow-up to complete in 2023.